(untitled) (Journal of Medical & Health Sciences Review, 2025)
Gastroenteritis remains a leading cause of morbidity and mortality in children, particularly in developing countries. This study aimed to investigate the prevalence, associated risk factors, clinical features, and bacterial causes of gastroenteritis in children from District Mardan, Khyber Pakhtunkhwa, Pakistan. A cross-sectional study was conducted on 250 pediatric patients presenting with symptoms of gastroenteritis. Clinical data were collected through structured questionnaires and physical examination. Stool samples were analyzed macroscopically and microscopically, followed by bacterial culture on selective media. Molecular identification of Salmonella spp., Shigella spp., and EPEC was performed using Polymerase Chain Reaction (PCR) targeting invA, ipaH, and eaeA genes, respectively. Diarrhea (100%), vomiting (72%), and fever (68%) were the most common clinical symptoms. Bacterial pathogens were isolated in 52 (Salmonella spp.), 33 (Shigella spp.), and 47 (EPEC) cases, with PCR confirmation rates of 94.2%, 93.9%, and 95.7% respectively. The highest prevalence occurred during summer (38.4%), and significant risk factors included lack of handwashing, untreated water use, poor sanitation, and low parental education. Form the statistical analysis it is confirmed that relations among these variables and infection risk (p < 0.05). The result shows a high intensity of gastroenteritis among children in Mardan District, strongly influenced by environmental and socioeconomic factors.